2021
DOI: 10.1590/0001-3765202120201022
|View full text |Cite
|
Sign up to set email alerts
|

Anurans trophic dynamic and guild structure in tropical dry forests of the Caribbean region of Colombia

Abstract: Studies on the exploitation of trophic resources allow to establish interactions between predators and predator-prey, and this dynamic can present fl uctuations over time and space. We analysed stomach contents of 19 anuran species from tropical dry forests of Colombia, quantifi ed the overlap between species and identifi ed anuran trophic guilds. Most of the species were generalists in diet (89.5%), some with strong prey dominance and only two species were classifi ed as specialists. Two anurans guilds were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Granted, other factors may have contributed to the difference between these studies, but it has been demonstrated that the level of taxonomic resolution can influence assumptions of prey utilization [ 34 ]. Dietary overlap appears substantially higher when the taxonomic resolution of prey is low and a decrease in overlap can be revealed with higher prey resolution [ 34 , 78 , 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Granted, other factors may have contributed to the difference between these studies, but it has been demonstrated that the level of taxonomic resolution can influence assumptions of prey utilization [ 34 ]. Dietary overlap appears substantially higher when the taxonomic resolution of prey is low and a decrease in overlap can be revealed with higher prey resolution [ 34 , 78 , 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most researchers have classified cane toads as indiscriminate, opportunistic, and/or generalist feeders based on ordinal or, at best, familial prey identifications and assumed that their diet is representative of the prey available in the respective study areas. Many of these studies have nonetheless identified beetles and ants as the dominant food items and a few have even suggested a preference for these prey items [ 80 , 81 ]. However, establishing this species’ foraging strategy and testing for food preferences requires the quantification of prey availability and efforts such as these are lacking in cane toad diet studies [ 10 ].…”
Section: Discussionmentioning
confidence: 99%